VOCATIONAL SCHOOL READINESS TO SUPPORT CREATIVE INDUSTRY DEVELOPMENT - Rida Perwita Sari; Dian Anita Nuswantara; Sri Setyo Iriani; Sanaji (Journal of Innovation Research and Knowledge, 2022)
This study explore how the employment of vocational school perceive towards the quality of the graduates. By identifying the quality of Vocational School graduates it is expected to be able to identify the quality gap produced with the required quality. Using qualitative approach, 14 informants were interviewed within 4 phase focus group discussion to reach their perception on the graduates quality. This research found that vocational study were contribute to the number of job less at young age. But, it is not because they didn’t have competencies needed but more on economic situation that push companies to be more efficient in recruiting new employee. Eventhough, the vocational school still have work to do that is give the students such soft competencies that makes them mature and ready to work as professional in terms of responsibility and commitment to his or her company.